2014
DOI: 10.5433/1679-0359.2014v35n5p2251
|View full text |Cite
|
Sign up to set email alerts
|

Salinidade na qualidade fisiológica em sementes de Brassicas oleracea L. var. itálica

Abstract: ResumoA demanda por sementes de hortaliças com alta qualidade e a obtenção de mudas vigorosas tem aumentado nos últimos anos, pois estas características constituem fatores determinantes do êxito da produção. O aproveitamento de algumas áreas como as de regiões áridas e semiáridas esbarra em alguns obstáculos como a salinidade e o potencial de sodicidade da água, utilizada na irrigação, cuja finalidade principal é proporcionar umidade adequada para o crescimento e desenvolvimento das plantas, visando aumentar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
2
6
0
3
Order By: Relevance
“…Stefanello, Neves, Abbad, and Viana (2015), also researching S. hispanica seeds, observed that germination and vigor were compromised by an increase in the concentration of salts. Similar results were found in broccoli seeds by Lopes et al (2014); in tomato seeds by Silva Júnior et al (2014); in beet seeds by Bernardes, Mengarda, Lopes, Nogueira, and Rodrigues (2015); and in cabbage by Oliveira et al (2015).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Stefanello, Neves, Abbad, and Viana (2015), also researching S. hispanica seeds, observed that germination and vigor were compromised by an increase in the concentration of salts. Similar results were found in broccoli seeds by Lopes et al (2014); in tomato seeds by Silva Júnior et al (2014); in beet seeds by Bernardes, Mengarda, Lopes, Nogueira, and Rodrigues (2015); and in cabbage by Oliveira et al (2015).…”
Section: Resultssupporting
confidence: 84%
“…Under high temperature conditions, there is an increase in seed metabolism, leading to greater soaking during the germination process. Thus, due to the high concentrations of salts present in the water and in the substrate, the absorption of the saline solution caused the seedlings to have inadequate supplies of nutrients because of the ionic imbalance resulting from excess Na + and Clions (Munns & Tester, 2008;Taiz & Zaiger, 2013;Lopes, Nascimento, Barbosa, & Costa, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the increase in the concentration of NaCl ions causes toxicity to plants and may cause damages to the radicle, thus limiting the seed imbibition process and the absorption of water by the plantlet (Munns and Tester, 2008;Voigt et al, 2009;Taiz and Zaiger, 2013). Similar results were observed in other vegetables such as melon (Secco et al, 2010), broccoli (Lopes et al, 2014), beet (Oliveira et al, 2015a) and cabbage (Oliveira et al, 2015b).…”
Section: Resultssupporting
confidence: 79%
“…A high concentration of salts is a stress factor for plants because water is osmotically retained in the salt solution. Therefore, the increase in salt concentration makes water less available to plants (Lopes et al, 2014). Species can adapt to salinity, but when they are sown in salt substrates, there is first a decrease in water uptake, which consequently reduces the speed of their physiological and biochemical processes.…”
Section: Resultsmentioning
confidence: 99%